Progesterone therapy in the prevention of pregnancy loss - Altaiam, Amani A.; Almomani, Jackleen R. (International Journal Of Community Medicine And Public Health, 2025)
Pregnancy loss, including early miscarriage and recurrent pregnancy loss (RPL), is a significant concern in reproductive health. Progesterone, a key steroid hormone, plays a critical role in preparing the endometrium, modulating immune tolerance, and maintaining uterine quiescence. This narrative review explores the current evidence on the mechanisms of progesterone action, its clinical efficacy in preventing pregnancy loss, available routes of administration, international guideline recommendations, and emerging therapeutic strategies. Randomized controlled trials (RCTs) notably the progesterone in spontaneous miscarriage (PRISM) and progesterone in recurrent miscarriage (PROMISE) studies-have demonstrated mixed results, with benefits more apparent in women with a history of RPL and those experiencing early pregnancy bleeding. These findings are supported by recent meta-analyses, which suggest that treatment success may depend on proper patient selection and timing of intervention. Among administration methods, vaginal progesterone remains the preferred route due to its targeted endometrial effects and reduced systemic side effects. However, oral dydrogesterone, a synthetic progestin, has shown potential in improving patient adherence. Recommendations from major clinical guidelines including those from the National Institute for Health and Care Excellence (NICE), the American College of Obstetricians and Gynecologists (ACOG), and the International Federation of Gynecology and Obstetrics (FIGO)-differ slightly based on interpretation of available data and individualized care approaches. Emerging directions include novel synthetic progestins with enhanced receptor specificity, combination regimens incorporating progesterone with surgical or immunologic therapies, and biomarker-guided approaches involving serum progesterone and progesterone-induced blocking factor (PIBF) levels. Advances in genetic and molecular profiling offer further potential for personalized medicine. Further research is warranted to refine patient selection, establish standardized protocols, and ultimately improve pregnancy outcomes